Metafora Ati ‘Hati’ dalam Bahasa Jawa - Ema Rahardian (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2020)
Other than as a communication tool, language is also used as a means of thinking and expressing ideas. Such language functions with regard to language as a cognitive process. The lexical selection in the metaphor is able to embody how human experiences are reflected and how human cognition is described. This research concerns about the Javanesse ATI metaphor. This research intends to describe how the Javanesse people comprehend the concept heart through the metaphor. The data are metaphorical phrases that conceive the heart concept in various texts. The data includes spoken and written text. Thus, the data are analyzed by padan method and PUP technique. It shows that Javanesse ATI metaphor is conceptualized as human, animal, plant, and material.